Peranan Psikologi Olahraga dalam Pencapaian Prestasi Atlet Senam Artistik Kabupaten Sijunjung - Sri Gusti Handayani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study was to see the extent of the role of sports psychology in artistic gymnastics. This type of research is qualitative. Data were taken through observation and interviews using a Likert scale questionnaire given to athletes, and data analysis was carried out by descriptive analysis. The results showed that in the training of gymnastics in Sijunjung Regency, the psychological aspects of athletes which included emotion, intelligence, intelligence, tension, discipline, aggressiveness, self-confidence, motivation, were still in the less category, this was due to the lack of attention paid coach in fostering artistic gymnastics. Conclusion, the psychological aspect is very much needed in supporting the artistic gymnastics athlete's presentation Keywords: Psychology, Artistic Gymnastics, Athlete Achievement